The description of catalyst behaviour during transesterification of rapeseed oil - Formation of micellar emulsion - Hájek, Martin; Vávra, Aleš; Skopal, František; Straková, Anna; Douda, Miroslav (Elsevier, 2020)
The catalyst behaviour throughout transesterification catalysed by KOH was described. The unreacted catalyst was determined: its amount depends on the initial catalyst amount and the maximum (almost 60 wt%) was reached for usually used catalyst amount (0.8 wt% to oil). Although the reaction mixture contains quite high amount of ions (OH-, CH3O- and K+) formed from catalyst, the measured in-situ conductivity during transesterification was very low (about 2 mu S cm(-1)). The reason was the formation of micellar emulsion from soaps formed by side reaction, because their concentration exceeded the critical micellar concentration. The formation of emulsion was confirmed by determination of the particles size. The formed emulsion are the cause that significant part of the catalyst remains unreacted and has to be neutralised at the end of the reaction, which increases the production cost and so whole production is less environmental. It was found out that the micellar emulsion was destroyed by addition of methanol to the reaction mixture.
Popis chování katalyzátoru běhe transesterifikace řepkového oleje - Tvorba micelární emulze
Keywords: transesterification; methanol; conductivity; viscosity; micellar emulsion; transesterifikace; metanol; vodivost; viskozita; micelární emulze